Exploring the Relationship Between Leadership Styles and Employee Motivation in the Context of Contemporary Management - Djoko Soelistya; Naim, Sidrotun; Muliyati, Muliyati; Anshoriyah, Sofiyatul; Syafri, Muhammad (International Journal of Economics (IJEC), 2024)
The objective of this research is to examine the relationship between leadership styles and employee motivation in the context of contemporary management. This research employs a literature review approach to analyse various leadership theories, including transformational, transactional, autocratic, democratic, laissez-faire, and servant leadership. Each leadership style is evaluated in relation to employees' intrinsic and extrinsic motivation. The findings indicate that transformational and democratic leadership styles have the most significant influence on employees' intrinsic motivation, whereas transactional and autocratic leadership styles emphasize extrinsic motivation. This study contributes to contemporary management literature by providing insights into the importance of tailoring leadership styles to employees' motivational needs to achieve optimal performance.